PENGARUH GAME ONLINE TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS VIII DI MTs PPKP SAMPIT - Siti Halimah; Mahmu’ddin Mahmu’ddin; Sri Rahayu (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2021)
This research was conducted to determine the effect of online games on motivation and learning achievement in the class VIII social studies subject at MTs PPKP Sampit. The subjects in this study were students of class VIII MTs PPKP for the academic year 2020/2021  which consisted of 5 rooms totaling 163 students. The technique used in collecting research subjects is saturated sampling technique. The data collection technique used a questionnaire. The data analysis technique used is Path Analysis with the help of the SPSS 15 for windows program.The results of the study partially showed that the significance value was 0.023 <0.05, so HO was rejected and Ha was accepted, which means that the relationship between X and Z and Y as the control variable is significant (real). Based on the discussion in the partial correlation test above, it is known that the presence of the motivation variable as a control variable has an effect on the online game variable and student learning achievement. The coefficient of determination (R2) was obtained by the R Square value of 0.386 or 38.6% which indicated that the percentage of the contribution of the influence from the variables (online games and learning achievement) to the control variable (learning motivation) was 38.6%. The variation of the X and Z variables used is able to explain 38.6% of the variation in the control variable. While the remaining 61.4% was influenced by other factors.